Analisis Keterampilan Bercerita Berbantuan Kartu Bergambar Peserta Didik Kelas III SDN Mangkubumen Kidul No. 16 Surakarta - Cahyono, Yogi Bagus Dwi; Riyadi, Riyadi; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2023)
Abstract. This research aims to analyse the storytelling skills assisted by picture cards of third grade students of SDN Mangkubumen Kidul No. 16 Surakarta. This research used a qualitative approach with a descriptive method. The participants of this study were 10 students at SDN Mangkubumen Kidul No. 16 Surakarta. Data collection techniques were conducted by interview, observation, and documentation. Data analysis in this research used qualitative data analysis of the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results of this research indicate that students have good skills in telling stories from various aspects with a final score percentage of 86%, although there are still many things that need to be improved and improved again so that students have better storytelling skills.